2009
DOI: 10.1007/s11426-009-0121-0
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses of amphiphilic biodegradable copolymers of poly(ethyl ethylene phosphate) and poly(3-hydroxybutyrate) for drug delivery

Abstract: Biodegradable and amphiphilic triblock copolymers poly(ethyl ethylene phosphate)-poly(3-hydroxybutyrate)-poly(ethyl ethylene phosphate) (PEEP-b-PHB-b-PEEP) have been successfully synthesizedthrough ring-opening polymerization. The structures are confirmed by gel permeation chromatography and NMR analyses. Crystallization investigated by X-ray diffraction reveals that the block copolymer with higher content of poly(ethyl ethylene phosphate) (PEEP) is more amorphous, showing decreased crystallizability. The obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The modified polymeric membranes showed excellent biocompatibility with cells, proteins, tissues and blood. Similar works were also carried out by several other research groups [20][21][22][23][24].…”
supporting
confidence: 63%
“…The modified polymeric membranes showed excellent biocompatibility with cells, proteins, tissues and blood. Similar works were also carried out by several other research groups [20][21][22][23][24].…”
supporting
confidence: 63%
“…The PPP 522 copolymer formed rod assemblies with a length of ∼2 μm and a diameter of ∼1 μm (Figure a, enlargement). PHBV segments might be assembled into the hydrophobic core, and the hydrophilic PEG was distributed outside after solvent evaporation. , The assemblies were not quite uniform because of various molecular weights and the segment composition of the triblock copolymers. The PPP 522 –Ag–ZnO nanocomposite assemblies showed different morphologies (Figure b), and NPs agglomeration increased the variation of shapes and sizes.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Indeed, the IC50 of nanoparticles based on PEEP-b-PEG-b-PEEP evaluated on HEK293 cells were higher than 1 mg.mL -1 [82]. It was also reported that PNIPAAM-b-PHB-b-PNIPAAM based micelles did not induced a significant cytotoxicity on L929 cells in the concentration range of 2-500 mg.mL -1 [70].…”
Section: In-vitro Biocompatibility Of Phb-based Self-assembled Systemsmentioning
confidence: 94%
“…Up to 70% of the loaded drug was released in 25 d. In addition, the DLE decreased upon lowering the hydrophilic weight fraction because the stability of the self-assembled system was reduced [82].…”
Section: Encapsulation and Drug Release From Other Phb-based Micellesmentioning
confidence: 99%